2005
DOI: 10.1785/gssrl.76.1.49
|View full text |Cite
|
Sign up to set email alerts
|

Coseismic Strain and the Transition to Surface Afterslip Recorded by Creepmeters near the 2004 Parkfield Epicenter

Abstract: The M w 6 Parkfield earthquake at 11:15 local time, 28 September 2004 has dealt a possibly fatal blow to the notion that significant surface slip precedes earthquakes. In 1966, anecdotal reports of surface fissures along the fault zone had been reported in the preceding week, and a water pipe fractured 11.6 hours before the mainshock. This offered hope that substantial surface slip may have occurred had displacement sensors been in place to measure it. In the days, hours, and minutes prior to the 2004 Parkfiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 11 publications
1
12
0
Order By: Relevance
“…Afterslip has approached the surface but has not completely ruptured the most shallow layer as demonstrated by the steep but continuous displacement gradients along the EP segment (Figure 6). This type of temporal relationship between surface fractures and the main shock has also been observed after the 2004 Parkfield earthquake where direct observations and geodetic measurements have shown that surface slip was delayed (sometimes days after the main shock) depending on the proximity of coseismic fault rupture to the surface [ Bilham , 2005; Rymer et al , 2006]. We thus suggest that a significant, and possibly dominant, contribution to the development of surface fractures along the EP segment have been provided by postseismic slip on the patch C (Figure 13), where slip appears to have migrated immediately after the main shock [ Amoruso and Crescenti , 2009], and which, lately, controlled the development of the hanging wall syncline shown in Figure 6.…”
Section: Discussionmentioning
confidence: 64%
“…Afterslip has approached the surface but has not completely ruptured the most shallow layer as demonstrated by the steep but continuous displacement gradients along the EP segment (Figure 6). This type of temporal relationship between surface fractures and the main shock has also been observed after the 2004 Parkfield earthquake where direct observations and geodetic measurements have shown that surface slip was delayed (sometimes days after the main shock) depending on the proximity of coseismic fault rupture to the surface [ Bilham , 2005; Rymer et al , 2006]. We thus suggest that a significant, and possibly dominant, contribution to the development of surface fractures along the EP segment have been provided by postseismic slip on the patch C (Figure 13), where slip appears to have migrated immediately after the main shock [ Amoruso and Crescenti , 2009], and which, lately, controlled the development of the hanging wall syncline shown in Figure 6.…”
Section: Discussionmentioning
confidence: 64%
“…(d) The surface crack was measured over a length of 8 km, about one half of the total fault length. The lower amplitude of the field measurements with respect to the interferometry could indicate that some creep was underestimated in the field because it occurred off the main fault strand or rotation of en‐echelon cracks occurred [ Bilham , 2005]. …”
Section: Datamentioning
confidence: 99%
“…Furthermore, geodetic models of coseismic slip and afterslip on the fault surface suggest that afterslip started almost immediately after the earthquake rupture, was roughly complementary in spatial distribution to the coseismic slip, and led to a total seismic moment (coseismic slip plus afterslip) that was two to three times larger than the seismic moment for the coseismic slip (Johanson et al, 2006;Johnson et al, 2006;Murray and Langbein, 2006). At the southern end of the rupture, a creepmeter recorded strain associated with the coseismic slip, but surface slip in the form of en echelon cracks did not appear until at least four days after the earthquake (Bilham, 2005).…”
Section: Introductionmentioning
confidence: 99%